1989
DOI: 10.1104/pp.91.3.862
|View full text |Cite
|
Sign up to set email alerts
|

Water Deficits and Reproduction in Maize

Abstract: Reproductive development in maize (Zea mays L.) is vulnerable to plant water deficits during anthesis but becomes less sensitive as reproduction progresses. To determine whether changes in tissue water status correlated with the change in sensitivity, we examined the water potential (',), osmotic potential (*I.), and turgor of reproductive tissues during a short-term water deficit imposed at anthesis or mid-grain fill. Plants were grown in controlled environments in soil. At anthesis, leaf, husk, silk, and ova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(14 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…For example, in vitro growth conditions may induce the synthesis and accumulation of ABA due to a more negative 4t' than exists in vivo. In addition, a decrease in i1, can alter the growth potential of maize kernels by prematurely accelerating grain desiccation (24). Hastened development was also indicated in the current study, because the cell division rates declined earlier in kemels cultured in low 14' media than in the control (Fig.…”
Section: Discussionsupporting
confidence: 69%
“…For example, in vitro growth conditions may induce the synthesis and accumulation of ABA due to a more negative 4t' than exists in vivo. In addition, a decrease in i1, can alter the growth potential of maize kernels by prematurely accelerating grain desiccation (24). Hastened development was also indicated in the current study, because the cell division rates declined earlier in kemels cultured in low 14' media than in the control (Fig.…”
Section: Discussionsupporting
confidence: 69%
“…Similarly, in a field study of container-grown maize, no difference in kernel ,t, was found between control and water-limited plants, sampled as early as 6 days after anthesis (30). Other studies of maize have suggested that the effect of water deficit on kernel {4K may be greater at early stages of development (43). When water was withheld beginning at anthesis, K , 6 of unpollinated ovaries decreased from -0.5 to -1.0 MPa over a 6-d period, whereas midday 4', of leaves decreased from -0.5 to -1.75 MPa (43).…”
Section: Kernel Water Potentialmentioning
confidence: 88%
“…Whereas placenta is highly vascularized such that its water status can equilibrate with whole-plant water potential during a stress episode, endosperm is remote from vasculature and is hydraulically isolated to some extent. Such isolation was documented in studies where whole-plant water deficit substantially lowered water potential in leaves and floral tissues, whereas water potentials of whole maize kernels or embryos remained the same as controls (Westgate and Thomson Grant, 1989;Ober and Setter, 1990). Steep downhill gradients in water potential were found from pedicel phloem to the grain in wheat (Triticum aestivum), consistent with hydraulic isolation between vasculature and surrounding tissues (Fisher and CashClark, 2000).…”
Section: Placenta and Endosperm Respond Differently To Water Deficit mentioning
confidence: 90%
“…Stresses that occur soon after pollination coincide with the period of endosperm cell division. This phase is particularly sensitive to water deficit, whereas later phases of kernel development, when starch and zein synthesis are at their maximum, are usually less affected (Grant et al, 1989;Artlip et al, 1995;Mambelli and Setter, 1998). Water deficit during the first few days after pollination inhibits endosperm cell proliferation, which is well correlated with kernel size at maturity (Nicolas et al, 1985;Ober et al, 1991).…”
mentioning
confidence: 99%